2018
DOI: 10.13189/ujer.2018.061222
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five Personality Traits and Narcissism as the Predictors of Anxiety and Confidence before Archery Class Final Exam

Abstract: In the present study I investigated whether the big five personality traits together with narcissism may have ability to predict the anxiety and self-confidence in physical education teacher candidates immediately before archery course final exam. The sample consisted of 52 college student athletes ranging in age from 20 to 24. Participants first completed the measures of the Big Five personality traits and narcissism measures. Then, their anxiety and self-confidence levels were measured via 100 mm visual anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
3
0
5
Order By: Relevance
“…Nalaz koji se pokazuje kao konzistentan u istraživanjima jeste taj da neuroticizam pozitivno korelira sa testnom anksioznošću, bez obzira na to koji se model ličnosti u istraživanjima koristio (Fitch, 2004;Jayaraman & Subramanian, 2015;Khosravi & Bigdely, 2008;Liu et al, 2006;Schmidt & Riniolo, 1999;Zunhammer et al, 2013). Ovaj nalaz se objašnjava time što je kod ljudi sa izraženijim neuroticizmom vrlo primjetan pojačan rad limbičkog sistema, koji je odgovoran za emocionalno reagovanje i ima dejstva na pojavu testne anksioznosti (Dal, 2018). Nalazi za odnos ostalih osobina ličnosti sa testnom anksioznošću su nekonzistentni i razlikuju se od istraživanja do istraživanja (Asmali, 2017;Dal, 2018;Zhang et al, 2021).…”
Section: Osobine Ličnosti I Testna Anksioznostunclassified
See 1 more Smart Citation
“…Nalaz koji se pokazuje kao konzistentan u istraživanjima jeste taj da neuroticizam pozitivno korelira sa testnom anksioznošću, bez obzira na to koji se model ličnosti u istraživanjima koristio (Fitch, 2004;Jayaraman & Subramanian, 2015;Khosravi & Bigdely, 2008;Liu et al, 2006;Schmidt & Riniolo, 1999;Zunhammer et al, 2013). Ovaj nalaz se objašnjava time što je kod ljudi sa izraženijim neuroticizmom vrlo primjetan pojačan rad limbičkog sistema, koji je odgovoran za emocionalno reagovanje i ima dejstva na pojavu testne anksioznosti (Dal, 2018). Nalazi za odnos ostalih osobina ličnosti sa testnom anksioznošću su nekonzistentni i razlikuju se od istraživanja do istraživanja (Asmali, 2017;Dal, 2018;Zhang et al, 2021).…”
Section: Osobine Ličnosti I Testna Anksioznostunclassified
“…Ovaj nalaz se objašnjava time što je kod ljudi sa izraženijim neuroticizmom vrlo primjetan pojačan rad limbičkog sistema, koji je odgovoran za emocionalno reagovanje i ima dejstva na pojavu testne anksioznosti (Dal, 2018). Nalazi za odnos ostalih osobina ličnosti sa testnom anksioznošću su nekonzistentni i razlikuju se od istraživanja do istraživanja (Asmali, 2017;Dal, 2018;Zhang et al, 2021). Na primjer, neki autori (Fitch, 2004;Furnham, 2008) sugerišu da esktraverzija pozitivno korelira sa testnom anksioznošću, dok se u drugim istraživanjima (Asmali, 2017;Jayaraman & Subramanian, 2015;Liu et al, 2006) došlo do otkrića da ekstraverzija negativno korelira sa datim konstruktom.…”
Section: Osobine Ličnosti I Testna Anksioznostunclassified
“…The examination of teachers are mostly influenced by level of anxiety and their overall performance rather than teacheroriented pre-exam anxiety (Núñez-Peña, Bono & Suárez-Pellicioni, 2015;Dal, 2018). Pre-examination anxiety occurs as a result of different factors before the examination.…”
Section: Pre-examination Anxietymentioning
confidence: 99%
“…A comprehensive study by Dal, (2018) on the use of Big Five personality traits and narcissistic personality traits to predict preexamination anxiety and self-confidence indicated that teachers' high narcissism helps reduce anxiety and increases self-confidence before the examination. As is expected, the weight of an examination has led to anxiety about the situation and its consequences always undermine test performance (Ramirez & Beilock, 2011).…”
mentioning
confidence: 99%
“…Self-confidence correlates positively with narcissism in physical education students before the archery exam ( Dal, 2018 ). Moreover, self-report confidence is significantly related to extraversion and emotional stability ( Burns et al, 2016 ), resilience ( Brooks and Goldstein, 2003 ; Westmattelmann et al, 2021 ), optimism ( Westmattelmann et al, 2021 ), and conscientiousness ( Matsumoto et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%